Penerapan Model Pembelajaran Make A Match pada Mata Pelajaran Matematika Siswa Kelas III SD - Selvy Ayu Juwita; Aswarliansyah Aswarliansyah; Andriana Sofiarini (Journal of Elementary School (JOES), 2023)
This study aims to determine the completion of Mathematics learning outcomes for third grade students at SD Negeri Kertosari. The research method used is in the form of Pre-Experimental Design. The population was all third grade students at SD Negeri Kertosari and at the same time the research sample totaling 17 students. Data collection was carried out using saturated sampling technique. The data collected was analyzed using a test. Based on the results of data analysis with a significant level of α = 5% and dk = 16, it shows that Zcount = 3.18 and Ztable = 1.64 (Zcount > Ztable). Thus it can be concluded that the mathematics learning outcomes of class III students at SD Negeri Kertosari after the Make A Match learning model was applied were complete. The average student final test score was 80.29 and the percentage of students who passed was 13 students (76.47%). Keywords: Learning Model ,Make A Match, Mathematics